Islamic philosophy in the pedagogy of landscape architecture: study on studio-based subject - Othman, Jamilah; Sarkawi, Azila; Mansor, Mazlina (2011)
The pedagogy that responds to the Islamic philosophy is designed to produce better quality of intellectuals, professionals and scholars whose practice/work always refers to the teaching of Islam. Thus, the Islamic values stressed at both the kulliyyahs (faculties) and departmental levels are anticipated to produce insan (human) with acceptable adab (etiquette) and conduct. For instance, the International Islamic University Malaysia (IIUM) has realised this pedagogy by intertwining the tawhidic principle (declaration of one God) with the courses offered by the university. The pedagogy explains the integration of the Islamic revealed knowledge (e.g. tawhidic principles) with the acquired knowledge (e.g. professional knowledge) as an approach towards a holistic education. In relation to that, this paper intends to present the outcomes of the pedagogy as inspired in the programme‟s course outline. The focus of the study was directed to a studio-based subject; e.g. ALA 1202 Landscape Architecture Design II. The subject is one of the core subjects designed for the Bachelor programme of Landscape Architecture (LA) offered by the Department of Landscape Architecture (DoLA) of Kulliyyah of Architecture and Environmental Design (KAED), IIUM. Thus, a pilot study was used to evaluate the workability of the pedagogy that has concerned for the Islamic philosophy. Parallel to that, the study had imposed the Islamic teaching in the content of the project briefs (written instructions). These were handouts given to students as assignment for the selected studio based class. Descriptive evaluation was then used to assess the practicality of the pedagogy. The purpose of the pilot study was to identify the issues that need to be rectified, so that, improvement on the teaching of studio-based subjects can be done. Findings show that the pedagogy of LA that instilled the Islamic philosophy based on both etiquette of delivering lesson, input lectures and project brief had contributed several implications; e.g. design solutions that had concern for nature and better understanding on the role of a landscape architect towards his environment. Importantly, result shows that the Islamization of human knowledge through the pedagogy of LA needs further improvement and assessment.